The Influence of Public Accountability, Service Performance and Administrative Information Systems for Producing E-KTP on Community Satisfaction (Case Study at the Nganjuk Regency Population and Civil Registration Service) - Maharanto S; Muhammad Ali Lutfi; Ambarwati; Wiwin Alief Bachtiar (IAEI, 2023)
This research addresses the misappropriation of government funds allocated to public service agencies, specifically focusing on the Nganjuk Regency Population and Civil Registration Service in managing expenditures for community services. The study aims to enhance fund allocation transparency and effectiveness by examining the impact of public accountability, service performance, and the administrative information system (SIAK) for e-KTP issuance on community satisfaction. Employing a quantitative approach with a statistical description, the researchers randomly sampled 100 respondents and collected primary data through Likert-scale questionnaires. The analysis involved descriptive statistics, instrument tests, classical assumption tests, and multiple linear regression. The empirical findings indicate a significant and positive influence of public accountability, service performance, and the population administration information system on community satisfaction during e-KTP issuance. This research contributes significantly to understanding the factors shaping community satisfaction and underscores the need for transparent fund utilization and efficient service delivery in public agencies like DISPENDUKCAPIL